2015
DOI: 10.1002/ep.12224
|View full text |Cite
|
Sign up to set email alerts
|

Char‐supported Fe–Zn–Cu sorbent prepared by ultrasonic‐assisted impregnation for simultaneous removal of H2S and COS from coke oven gas

Abstract: Lignite char supported Fe–Zn–Cu sorbents were prepared by ultrasonic‐assisted impregnation method for the simultaneous removal of H2S and COS from coke oven gas (COG). Sulfidation experiments were carried out in a fixed‐bed quartz reactor using simulated COG. The results showed that the addition of Cu can significantly increase the sulfidation reactivity of char‐supported Fe–Zn sorbents. Char‐supported Fe–Zn–Cu sorbents with Fe:Zn:Cu molar ratio of 2:1:0.5 could simultaneously remove H2S and COS in the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The broad Fe 2p 3/2 peak for the sorbent after sulfidation (see Figure ) was divided into two peaks at 712.1 and 709.8 eV, which were assigned to FeS and FeS 2 , respectively . Moreover, the broad Fe 2p 3/2 peak of the fresh and regenerated sorbents (see Figure ) was divided into two peaks at 710.2 and 712.5 eV, which were assigned to Fe 3 O 4 and Fe 2 O 3 , respectively. , It can be seen in Figure b that the main binding energy of Zn 2p 3/2 in the sorbent after sulfidation is 1021.7 eV, which was assigned to ZnS, ,, while the Zn 2p 3/2 peaks of the fresh and regenerated sorbents were observed at 1022 eV (assigned to ZnO). ,, As seen in Figure , the main binding energies of Cu 2p 3/2 in the fresh and regenerated sorbents were 932.6 and 933.3 eV (assigned to CuO and CuFe 2 O 4 , respectively), while the Cu 2p 3/2 peaks of the sorbent after sulfidation were displayed at 932.4 and 932.5 eV (assigned to CuS and Cu 2 S, respectively) . These results were well in agreement with the XRD analysis results.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The broad Fe 2p 3/2 peak for the sorbent after sulfidation (see Figure ) was divided into two peaks at 712.1 and 709.8 eV, which were assigned to FeS and FeS 2 , respectively . Moreover, the broad Fe 2p 3/2 peak of the fresh and regenerated sorbents (see Figure ) was divided into two peaks at 710.2 and 712.5 eV, which were assigned to Fe 3 O 4 and Fe 2 O 3 , respectively. , It can be seen in Figure b that the main binding energy of Zn 2p 3/2 in the sorbent after sulfidation is 1021.7 eV, which was assigned to ZnS, ,, while the Zn 2p 3/2 peaks of the fresh and regenerated sorbents were observed at 1022 eV (assigned to ZnO). ,, As seen in Figure , the main binding energies of Cu 2p 3/2 in the fresh and regenerated sorbents were 932.6 and 933.3 eV (assigned to CuO and CuFe 2 O 4 , respectively), while the Cu 2p 3/2 peaks of the sorbent after sulfidation were displayed at 932.4 and 932.5 eV (assigned to CuS and Cu 2 S, respectively) . These results were well in agreement with the XRD analysis results.…”
Section: Resultsmentioning
confidence: 92%
“…They suggested that 11 metal elements (i.e., Fe, Zn, Mo, Mn, V, Ca, Sr, Ba, Co, Cu, and W) have the thermodynamic feasibility for desulfurization. Currently, Fe 2 O 3 , ZnO, CuO, and MnO have been widely used as desulfurization sorbents to remove sulfur species from gas streams. By comparison to the development of single-element sorbents, various composite metal oxides, , such as Co 3 O 4 /TiO 2 , Zn–Fe, Cu–Fe, Zn–Fe–Mn, and Fe–Zn–Ce, have been tested in other studies. Their results suggested that the reactivity and regenerability of these sorbents were improved when the composite metal oxides were supported on suitable supports, such as activated carbon fibers (ACFs), activated carbons (ACs), and activated chars. …”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that both the H 2 S loading of IMC and INC are increased as the humidity increasing, indicating humidity can strengthen the catalyst property. Because of high humidity, the water film can be formed quickly on the carbon surface, and increase the dissolution of H 2 S and O 2 , which enhances the catalytic oxidation of H 2 S 8,9 . Comparing IMC and INC, INC has better catalytic performance than IMC, which is also attributed to the dispersed catalyst and large contacting surface.…”
Section: Resultsmentioning
confidence: 99%
“…There are many ways to achieve the desulfurization, like the biological treatment, 4 wet scrubbing, 5 low temperature plasma technology, 6 advanced oxidation, 7 special activated carbon adsorption. [8][9][10] Among these methods, adsorption is a high-efficiency and economic way to remove hydrogen sulfide. [11][12][13] Generally, raw carbon has bad performance for H 2 S adsorption, while activated carbon loaded with catalysts has better performance for H 2 S adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation